POLA KONSUMSI PANGAN PADA RUMAH TANGGA PETANI DI DESA RUGUK KECAMATAN KETAPANG KABUPATEN LAMPUNG SELATAN - Nadia Ariandika Arlin; Bustanul Arifin; Ani Suryani (Lampung University, 2017)
This study aims to determine the household of farmers' level of poverty, the food consumption pattern of farmer’s household according to the score of Desirable Dietary Pattern (DDP), and the factors that affect the score of DDP of the farmers' household in Ruguk Village Ketapang Sub District South Lampung Regency. The research was conducted in Ruguk Village, Ketapang Sub District of South Lampung Regency. Sixty seven respondents were obtained by simple random sampling method. In this study, to determine food consumption pattern used a score of Desirable Dietary Pattern (DDP) in farmers' household and to know the factors that affect the score of DDP used multiple linear regression analysis. The food consumptin pattern of farmers' household in Ruguk Village, South Lampung with score size of Desirable Dietary Patternwas good enough (88,25) and still under the recommended score of Desirable Dietary Pattern (DDP) and the variables that significantly affected PPH farmers' household were expenditure and the number of members of family. Key words: poverty, food consumption patterns, desirable dietary pattern